Capacity Building of The National Police in The Implementation of the 2023-2024 Mantap Brata Tinombala Operation in The Central Sulawesi Regional Police - Roynaldo Ondey, Hezron; Nuraisyah, Nuraisyah; Haryono, Dandan (International Journal of Social Science, Education, Communication and Economics, 2024)
The purpose of this study is to find out the development of the institutional capacity of the National Police in the implementation of the 2023-2024 Mantap Brata Tinombala Operation in the Central Sulawesi Regional Police area. This study uses a qualitative approach with strategic case studies to collect data through observation, in-depth interviews, and documentation, involving five key informants from the Regional Police. The theoretical framework used is Grindle's theory and the concept of institutional capacity building that includes the dimensions of individuals, organizations, and systems. The results showed that the individual dimension had been effective with a good work culture and smooth communication, although some members still felt that they lacked relevant training. In the organizational dimension, the decision-making structure is democratic with strong synergy between the National Police, the community, and the government, but the increase in member participation in decision-making still needs to be considered. In the system dimension, rules and SOPs are clear, but periodic evaluations and internal supervision need to be improved to prevent deviations and increase transparency. The conclusion of this study shows that although many aspects have been effective, there is still room for improvement that can improve the overall performance in the implementation of Operation Mantap Brata Tinombala.